Fibroblast Growth Factor 1 Ameliorates Diabetes-Induced Liver Injury by Reducing Cellular Stress and Restoring Autophagy - Xu, Zeping; Wu, Yanqing; Wang, Fan; Li, Xiaofeng; Wang, Ping; Li, Yuying; Wu, Junnan; Li, Yiyang; Jiang, Ting; Pan, Xindian; Zhang, Xie; Xie, Longteng; et al. (Frontiers in Pharmacology, 2020)
Abstracts Background: Type 2 diabetes (T2D) is a metabolic dysfunction disease that causes several complications. Liver injury is one of these that severely affects patients with diabetes. Fibroblast growth factor 1 (FGF1) has glucose-lowering activity and plays a role in modulation of several liver injuries. Nevertheless, the effects and potential mechanisms of FGF1 against diabetes-induced liver injury are unknown. Methods: To further investigate the effect of FGF1 on diabetic liver injury, we divided db/db mice into two groups and intraperitoneally (i.p.) injected either with FGF1 at 0.5 mg/kg body weight or saline every other day for 4 weeks. Then body weights were measured. Serum and liver tissues were collected for biochemical and molecular analyses. Results: FGF1 significantly reduced blood glucose and ameliorated diabetes-induced liver steatosis, fibrosis and apoptosis. FGF1 also restored defective hepatic autophagy in db/db mice. Mechanistic investigations showed that diabetes markedly induced oxidative stress and endoplasmic reticulum stress and that FGF1 treatment significantly attenuated these effects. Conclusions: FGF1-associated glucose level reduction and amelioration of cellular stress are potential protective effects of FGF1 against diabetes-induced liver injury. Key words: Fibroblast growth factor 1 (FGF1); Diabetes; Liver injury; Oxidative stress; Endoplasmic reticulum (ER) stress